Seroprevalence, Seasonal Occurrence and Clinical Manifestation of Newcastle Disease in Rural Household Chickens in Plateau State, Nigeria - Musa, U.; Abdu, P.A.; Dafwang, I.I.; Umoh, J.U.; Saidu, L.; Mera, U.M.; Edache, J.A. (International Journal of Poultry Science, 2009)
A study on seroprevalence, seasonal occurrence and clinical manifestation of Newcastle Disease Virus (ND) among rural household chickens and Live Birds Markets (LBM) was conducted using haemagglutination Inhibition Test (HI) and questionnaires. A total of 1, 208 chickens reared under extensive management system in four Local Government Areas (LGAs) of Plateau State were used for the study. The seroprevalence of ND virus antibodies in rural chickens showed that there was no statistically significant (p > 0.05) difference among the four LGAs and of the 1,208 sera tested, 51.9% had detectable antibodies to NDV but only 14.1% of the chickens had HI antibody titre of > 4log2 which was considered as protective. About 86.2% of the chickens sampled were at risk of suffering from clinical ND. Newcastle disease outbreaks occurred year round in the villages sampled with the highest incidence of 86.6% observed from November to March (Dry season) and September to October, 8.31% (Pre-dry season). During outbreaks of ND, infected birds exhibit the following major clinical signs; nervous signs (32.4%), weakness (16.6%), whitish/greenish diarrhea (16.2%), coughing/sneezing 13.6%, anorexia 9.39% and others 11.8%. It was concluded that the prevalence of ND in the four LGAs of Plateau State is high. At the time of the study over 80% of rural chickens in Plateau State were at risk of dying from ND when exposed to a virulent NDV. It is therefore recommended that vaccination and improved management practices as a means of prevention against ND before the period of outbreaks should be instituted.